Improving Sleep Quality in Third Trimester Pregnant Woman: The Effect of Chamomile Aromatherapy - Ramadana, Rima Fitri; Antono, Sumy Dwi; Rahayu, Dwi Estuning; Hardjito, Koekoeh (Poltekkes Kemenkes Surakarta, 2025)
Background: Sleep quality during pregnancy decreases significantly as pregnancy progresses. Poor sleep quality can be addressed with various methods, including aromatherapy as a relaxation technique. Chamomile aromatherapy contains compounds that increase gamma-aminobutyric acid (GABA) receptor activity, thereby promoting muscle relaxation and inducing sleepiness. This study aims to assess improvement in sleep quality in third-trimester pregnant women after receiving chamomile aromatherapy. Methods: This study used a pre-experimental one-group pretest–posttest design. The sample consisted of 30 participants, all of whom were pregnant women in their third trimester. Data were collected using the Pittsburgh Sleep Quality Index (PSQI) questionnaire and an observation sheet. The chamomile aromatherapy intervention was administered before bedtime for 14 consecutive days by adding three drops of chamomile essential oil to a humidifier containing 100 ml of water, which was diffused for 10 minutes. Results: A total of 53.3% of respondents had poor sleep quality before the chamomile aromatherapy intervention, which increased to 53.3% with excellent sleep quality after the intervention. The results of the Wilcoxon Signed-Rank Test showed a statistically significant improvement in sleep quality (p = <0.001). The Wilcoxon Signed Rank Test showed a significant improvement in sleep quality (p = <0.001). Conclusion: Chamomile aromatherapy significantly improves sleep quality in third trimester pregnant women. Health workers, especially midwives and nurses, should provide education and guidance on the safe use of chamomile aromatherapy.